Variations in the Adoption and Use of Different Family Planning Methods and Implications: Evidence from a Cross-Sectional Study in Nigeria - Adebola, Femi B.; Ononokpono, Dorothy N.; Adebola, Olukemi G.; Ewemooje, Olusegun S.; Adediran, Adetola A.; Oboh, Ganiyu; Jibasen, Danjuma; Metiboba, Steve (ABUAD Journal of Social and Management Sciences, 2024)
Despite concerted efforts by all stakeholders to increase acceptability and access to modern family planning (FP) methods, the adoption and usage of family planning methods have remained low, particularly in developing countries which place stringent conditions on achieving SDGs. Therefore, there is the need to understand variations in the adoption and use of FP and their implications to speed-up interventions in the right direction. The study used cross-sectional data collected between June and August 2022 in 2,817 households with 6,641 males and females of reproductive age successfully interviewed. Univariate, bivariate, and binary multivariate logistic regression model were used to model traditional and modern FP usage. Awareness was shown to be approximately two-thirds (62.8%) among respondents with main source of information being radio. Major methods of awareness are condom and pills. In terms of significant others’ support enjoyed, 43.5%, 38.5% and 39.5% enjoyed their mother, mother-in-law, and community support, respectively. Religion, region and parent’s parity were significant predictors of traditional method usage. Living in the North-Western region, increase in education, being gainfully employed, increase in years of marriage and exposure to media increase the use of modern methods of FP, whereas living in the rural areas (AOR = 0.76; CI = 0.58-1.00) and partner FP approval (AOR = 0.64; CI = 0.48-0.85) significantly reduce usage. Diverse variations have been identified in the adoption and usage of FP. To improve utilisation, appropriate education and accurate information through radio and mass media must be provided in rural areas and regions where FP usage is low.